Contempt of Court in Renewal of Indonesian Criminal Law Based on Pancasila - M Musmuliadin; Erlyn Indarti; Nur Rochaeti (Universitas Muhammadiyah Surakarta, 2022)
The act of harassment against the administration of justice is not new. However, these acts have been happening more frequently since the freer reform era. Actions and situations that occur in court such as obstructing and making noise during the trial process can be said to be Contempt of Court (